1996
DOI: 10.1021/jp951865f
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Conformations of N-Acetyl-N‘-methyl-l-alaninamide from Vibrational Raman Optical Activity

Abstract: Experimental and ab initio theoretical vibrational Raman optical activity (VROA) spectra are presented for N-acetyl-N‘-methyl-l-alaninamide (NANMLA), in order to determine the predominant conformations of this molecule in the solution phase. The experimental spectra were obtained in three different solvents, CHCl3, H2O, and D2O. The ab initio VROA spectra were predicted for nine different conformations of NANMLA optimized with the 6-31G* basis set. The vibrational frequencies and normal modes for all nine conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 26 publications
3
82
0
Order By: Relevance
“…In 1980, based on NMR and CD measurements, Madison and Kopple 31 concluded that P II -like (corresponding to the ␤-conformer in this article) and ␣ R conformers were the dominant species in water. In contrast, based on the experimental and computational studies of vibrational Raman optical activity of AD in CHCl 3 , H 2 O, and D 2 O, Deng et al, 27 in 1996, proposed the presence of C7 eq OC 5 (i.e., ␤ in the present article), C7 eq , and ␣ R in aqueous solution and C7 eq -C 5 and ␣ R in chloroform. The Weisshaar group 7,30 found that the structure of ␤ ϩ 4H 2 O, computed by Han et al, 11 fits to their dipolar coupling data best, and concluded that the P II -like conformer may be the primary species.…”
Section: Comparison With Experimental and Other Theoretical Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In 1980, based on NMR and CD measurements, Madison and Kopple 31 concluded that P II -like (corresponding to the ␤-conformer in this article) and ␣ R conformers were the dominant species in water. In contrast, based on the experimental and computational studies of vibrational Raman optical activity of AD in CHCl 3 , H 2 O, and D 2 O, Deng et al, 27 in 1996, proposed the presence of C7 eq OC 5 (i.e., ␤ in the present article), C7 eq , and ␣ R in aqueous solution and C7 eq -C 5 and ␣ R in chloroform. The Weisshaar group 7,30 found that the structure of ␤ ϩ 4H 2 O, computed by Han et al, 11 fits to their dipolar coupling data best, and concluded that the P II -like conformer may be the primary species.…”
Section: Comparison With Experimental and Other Theoretical Resultsmentioning
confidence: 62%
“…7,[27][28][29][30][31] As we will detail in the Results and Discussion section, the experimental conclusions were not consistent. Although the alanine dipeptide is an important test system, there has been no cutting-edge study on it, especially with regard to the effects of solvation.…”
Section: Introductionmentioning
confidence: 89%
“…The four peaks of 1660, 1640, 1618, and 1604 cm Ϫ1 were determined by the second derivative analysis in a similar manner as the skeletal stretching mode. From the results by Deng et al 4 and Han et al, 5 the peaks around 1660 and 1640 cm Ϫ1 were assigned to the ␣ R and P II conformations, respectively.…”
mentioning
confidence: 95%
“…The four peaks of 842, 859, 885, and 924 cm Ϫ1 were determined by the second derivative analysis of the original spectra. Deng et al 4 and Han et al 5 have studied on the conformation of AAlaMA in some model systems of aqueous solution by the ab initio MO method. They assigned the peaks around 860 and 925 cm Ϫ1 to the P II and the ␣ R conformations, respectively.…”
mentioning
confidence: 99%
“…The conformation-sensitive bands in the spectra of polypeptides in water are amide I vibrations, [10,11] amide II vibrations, [12,13] NH stretching vibrations (amide A), [14,15] C α D vibrations, [16] and skeletal vibrations observed in Raman spectra. [17,18] However, the most frequently used bands for structural determination are the amide I and amide III bands.…”
Section: Introductionmentioning
confidence: 99%